Bringing the Social Back in: Some Suggestions for the Qualitative Study of Emotions - Kusenbach, Margarethe; Loseke, Donileen R. (Qualitative Sociology Review, 2013)
As a relatively new area of inquiry, it is not surprising that the research agendas and methodological tools of the sociology of emotions are still evolving. Our goal in this article is to offer new ideas toward emphasizing the social, as opposed to individual, dimensions of emotions in sociological research. What are the historical, cultural, and biographical structures and contexts of individual emotional experiences? What are the social and political antecedents of individual experience? What are the origins of social and cultural frameworks shaping individual experience? What are the social and political consequences of individual experiences? Broadly speaking, these questions are about how people make meanings from cultural resources, and about how these meanings make culture. And because these are questions about meaning, they necessarily require qualitative data and analytic techniques. The second section of the article, written by Loseke, conceptualizes and explores emotions as systems of meanings. Rather than focusing on unique individual experiences, Loseke’s starting point is the shared ideas and rules regarding emotions within a culture, and their manifestations in widely circulating narratives. The ensuing analysis focuses on the symbolic and emotion codes (e.g., victim) and structures of such stories, and on the work they do for individuals and for society as a whole. The third part of the article, written by Kusenbach, begins with individual emotional experiences, yet seeks to account for the larger cultural patterns (life stories) that provide them with meaning. Kusenbach’s research shows that residents of mobile homes, a stigmatized type of housing, employ a range of cultural narratives that furnish both negative and positive emotional experiences surrounding their place of living. In sum, it is argued that both approaches generate new questions and insights, new kinds of data, and new methodological tools for a more sociological study of emotions.